Drug Utilization and Evaluation of Proton Pump Inhibitors at Tertiary Care Hospital of Southern Rajasthan - Malviya, Chetan; Parihar, Narendra Bheemraj; Dhakar, Manish; Vishnoi, Sunil; Kumar, Ritesh; Rathore, Mahendra Singh; Shrimali, Lalit (Indian Journal of Pharmacy Practice)
Introduction: Proton Pump Inhibitors (PPIs) are among the most frequently prescribed drugs for the management and prevention of acid-related gastrointestinal disorders. Although PPIs are effective and well tolerated, their widespread and often empirical use has raised concerns regarding inappropriate prescribing, prolonged therapy, polypharmacy, and potential adverse effects. Drug utilization studies play a crucial role in evaluating prescribing trends and promoting rational use of PPIs in hospital settings. Materials and Methods: A prospective observational study was conducted over six months in the Department of General Medicine of a tertiary care teaching hospital. A total of 170 adult inpatients aged 18-60 years who were prescribed proton pump inhibitors were included. Data on socio-demographic characteristics, prescribing patterns, dosing frequency, number of drugs per prescription, and concomitant medications were collected using a structured data collection form. Utilization of PPIs was assessed using World Health Organization prescribing indicators and the Anatomical Therapeutic Chemical/ Defined Daily Dose (ATC/DDD) methodology, expressed as defined daily dose per 100 bed-days (DDD/100 bed-days). Descriptive statistical methods were applied for data analysis. Results: Most patients belonged to the 47-60 years age group, with a predominance of male patients. Pantoprazole was the most frequently prescribed proton pump inhibitor, followed by rabeprazole. Once-daily dosing was commonly observed. Polypharmacy was prevalent, with the majority of patients receiving six or more medications during hospitalization. Antibiotics, antiemetics, and non-steroidal anti-inflammatory drugs were the most commonly co-prescribed drug classes. Utilization analysis revealed higher DDD/100 bed-days for pantoprazole compared to other PPIs. Conclusion: The study demonstrates extensive use of proton pump inhibitors among hospitalized patients, with frequent polypharmacy and concurrent drug use. Regular prescription audits and adherence to evidence-based guidelines are essential to ensure rational PPI use and improve patient safety.
Keywords: Define Daily Dose (DDD); Drug utilization study; Polypharmacy; Proton-Pump; Inhibitors (PPIs); Rational drug use; Zollinger-Ellison Syndrome (ZES)